Indigenous Contributions to Arctic Biodiversity Conservation, Circumpolar Arctic, (2017-2021) - Victoria Qutuuq Buschman (Arctic Data Center, 2022)
A significant percentage of the earth’s surface is owned, used, and managed by Indigenous peoples, securing Indigenous communities a critical role in current and future biodiversity conservation efforts. Within the Arctic, Indigenous communities are already contributing knowledge, labor, resources, and time to research, management, and conservation governance. This dissertation research examines the contributions of Indigenous knowledge and communities to biodiversity conservation in the Arctic in three areas, (1) how the evolution of conservation planning and knowledge co-production facilitates the ability of Indigenous communities to contribute to current research and conservation efforts, (2) to what extent Indigenous communities use lands, waters, and species within Arctic protected areas and to what extent they are invited to engage in management efforts, and (3) how forwarding a new framework for co-productive conservation supports partnerships with Indigenous communities, knowledge, and governance can aid in the development of ethically-conscious, culturally-relevant, and fully knowledge-based conservation efforts. Results show that Indigenous communities are critical partners in conservation, bring valuable knowledge and information to the creation of shared evidence bases, and are prepared to lead new and innovative conservation efforts when there are opportunities to support both subsistence and conservation targets and goals.